Analysis of effect of promotion and word of mouth on purchase decision: Case of student University of Muhammadiyah Sumatera Utara - Mutia Arda (Proceedings of AICS - Social Sciences, 2017)
Muhammadiyah University of North Sumatra is one of the educational institutions in Muhammadiyah association. Marketing activities affect buyers' decisions to use services when they need them. Purchasing decisions are essentially related to